Archival training for employees of the Sungai Pinang Luar Village Office, Samarinda City - Muhammad Nawawi; Besse Asniwati; Suminto Suminto (Community Empowerment, 2022)
Apart from being an organizational asset, properly organized archives are also useful as material for making quick and accurate organizational decisions. The proper implementation of archives can reduce the number of management errors that the organization will make. Human resources, standard archive handling procedures, and archive storage systems are some of the archival issues at the Sungai Pinang Luar Village Office. This training resulted in the management of archives using a problem-based classification system and the recovery of archives using an alphabetical system.